HYDROCARBON GASES AND HELIUM ISOTOPES IN THE PALEOZOIC ALKALINE-ULTRAMAFIC MASSIFS OF THE KOLA PENINSULA - Ikorsky S.V.; Avedisyan A.A. (My University, 2007)
Hydrocarbon gases (HCG) were studied in fluid inclusions from seven alkaline-ultramafic massifs of the Kola Peninsula. All the massifs (Sebljavr, Kovdor, Lesnaya Varaka, Ozernaya Varaka, Vuorijarvi, Turii Peninsula, and Salma) are central-type cratonic intrusions with ages of 360–410 Ma. Previous He isotopic investigations showed that the massifs have high 3He/4He ratios (up to 3.3 × 10−5), which are usually higher than the upper mantle value. Similar to He, HCG were extracted by crushing. The HCG were analyzed for CH4 (main component), C2H6, and C3H8. A comparison of HCG component contents with He isotope abundances and ratios showed that the HCG were probably not supplied by mantle-derived melts. Their formation during a postmagmatic stage at relatively low temperatures is our favored model.
Keywords: Paleozoic; Paleozoic::Devonian; Палеозой::Девонская